Analisis Kebutuhan Bahan Ajar Berbasis Digital pada Mata Pelajaran Matematika dalam Meningkatkan Kompetensi Lulusan Siswa di MTs Negeri 2 Kota Bengkulu - Govi Saputra; Dandun Setiawan Fambudi (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract: This study aims to analyze the need for digital-based teaching materials in mathematics subjects to improve the competency of student graduates at MTsN 2 Bengkulu City. This study used a descriptive qualitative method and was carried out for three months, from February to April 2026. The research subjects included the Principal, the Deputy Curriculum, mathematics teachers, students, and IT operators. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman theory (data reduction, presentation, and conclusion drawing). Data validity was maintained through triangulation of sources and methods. Research findings indicate an urgent need for three types of digital teaching materials: (1) Interactive e-modules with engaging visualizations to enhance conceptual understanding (C3) in contextual problem-solving; (2) Device-based digital educational games to motivate students and reduce classroom boredom; and (3) Educational videos that allow students to repeat tutor explanations to enhance contextual understanding and presentation skills. Currently, student competency has only reached the understanding level (C2) and remains weak in the skills and active attitudes aspects. The integration of digital technology in the form of e-modules, educational games, and videos is essential for transforming mathematics learning from abstract concepts into real-world experiences. The use of these digital media has been theoretically and empirically proven in the field to support the achievement of Graduate Competency Standards (SKL) in the domains of student attitudes, knowledge, and skills.Keywords: Needs Analysis, Digital Teaching Materials, Mathematics, Graduate Competencies. Abstrak: Penelitian ini bertujuan untuk menganalisis kebutuhan bahan ajar berbasis digital pada mata pelajaran matematika guna meningkatkan kompetensi lulusan siswa di MTsN 2 Kota Bengkulu. Penelitian ini menggunakan metode kualitatif deskriptif yang dilaksanakan selama tiga bulan, dari Februari hingga April 2026. Subjek penelitian meliputi Kepala Madrasah, Waka Kurikulum, guru matematika, siswa, dan operator IT. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan teori Miles dan Huberman (reduksi, penyajian data, dan penarikan kesimpulan). Validitas data dijaga melalui triangulasi sumber dan metode. Temuan penelitian menunjukkan adanya kebutuhan mendesak terhadap tiga jenis bahan ajar digital: (1) E-modul interaktif dengan visualisasi menarik untuk meningkatkan pemahaman konsep (C3) dalam pemecahan masalah kontekstual; (2) Game edukasi digital berbasis gawai untuk memotivasi siswa dan mengurangi kebosanan di kelas ; dan (3) Video edukasi yang memungkinkan siswa mengulang penjelasan tutor guna meningkatkan pemahaman kontekstual dan kemampuan presentasi. Saat ini, kompetensi siswa baru mencapai tingkat memahami (C2) dan masih lemah pada aspek keterampilan serta sikap aktif. Integrasi teknologi digital dalam bentuk e-modul, game edukasi, dan video sangat esensial untuk mentransformasi pembelajaran matematika dari konsep abstrak menjadi pengalaman nyata. Penggunaan media digital ini terbukti secara teoritis dan empiris di lapangan mampu mendukung pencapaian Standar Kompetensi Lulusan (SKL) pada ranah sikap, pengetahuan, dan keterampilan siswa.Kata Kunci : Analisis Kebutuhan , Bahan Ajar Digital , Matematika , Kompetensi Lulusan.